Clinical Analysis of Ten Cases of Neuralgic Amyotrophy - Remi Morimoto; Mutsumi Iijima; Kunio Toda; Kazuo Kitagawa (Tokyo Women's Medical University Journal, 2024)
Background: Neuralgic amyotrophy (NA) typically develops with neuralgia in the upper limbs and causes localized muscle atrophy after pain subsides. NA is not well known; thus, many patients face delayed diagnosis and treatment. Methods: We evaluated the initial symptoms, symptom duration, neurological findings, impaired nerves, treatment, and sequelae in patients with NA in our department between 2010 and 2020. Results: Ten patients had upper-limb NA. The suprascapular nerve was the most commonly affected nerve (n = 9). Needle electromyography revealed abnormal findings in all patients, and fibrillations/positive sharp waves at rest were observed in seven patients. Nerve conduction studies showed reduced motor or sensory nerve action potential amplitudes in six patients. Brachial plexus magnetic resonance imaging (MRI) revealed abnormalities in five patients. The mean duration from symptom onset to diagnosis was 142 days (median: 130 days), and the mean duration from the first visit to our department to diagnosis was 41 days (median: 20 days). Sequelae were observed in patients diagnosed 200 days after symptom onset. Conclusion: A combination of needle electromyography of the affected muscles, nerve conduction studies, and a special MRI technique (short tau inversion recovery MRI) may support the diagnosis of NA lesions, even in the subacute to chronic phase.